Having sex, becoming somebody: A qualitative study assessing (sexual) identity development of adolescents living with HIV/AIDS - Loos, Jasna; Nöstlinger, Christiana; Murungi, Irene; Adipo, Daniel; Amimo, Brenda; Bakeera-Kitaka, Sabrina; Oluoch, Dorothy; Mboi, Phyllis; Wobudeya, Eric; Vandenhoudt, Hilde; Buvé, Anne (Routledge, 2012)
A growing number of adolescents are living with HIV/AIDS. For their well-being and for prevention, age- and culturally appropriate interventions become increasingly important. This qualitative study was conducted as the ﬁrst step to develop a sexual and reproductive health (SRH) intervention. The study’s objective was to assess the impact of HIV and related contextual conditions on identity formation of adolescents living with HIV/AIDS (ALH) in the domains of physical, cognitive, social, and sexual development. Data were collected using focus group discussions (FGDs). Through HIV care centers in western Kenya and Greater Kampala, Uganda, we recruited 119 ALH aged 10–19 years, 54 of their caregivers, and 55 service providers for 28 FGDs. Following analytic induction principles, data analysis showed that many ALH had grown up in HIV-affected families in poverty. They reported experiencing long histories of illness and HIV-related stigma and discrimination, affecting their self-esteem. The physical changes of puberty, fueled by effective HIV treatment, symbolized a new start in life. The cognitive changes typical for adolescence enhanced their self-esteem, resilience, and belief in the future, particularly among older adolescents. In discovering their new social identity, ALH experimented with behaviors and norms, especially related to sexuality. ALH carefully examined the contrasting sexual norms of their peers, caregivers, and service providers and balanced them when developing their own sexual identity. For many ALH, sex is the way to become a social “somebody.” For some, having sex served to cope with the emotional pains of growing up with HIV. Sexual relationships also enabled some ALH to gain ﬁnancial and emotional independence. This study shows how ALH’s identity development is inﬂuenced by the individual and social consequences of HIV. Multiple factors contribute to the importance that ALH attribute to sexuality, which calls for comprehensive interventions addressing the broader context of positive living and SRH rights.
Keywords: Adolescents; HIV; Identity development; Sexuality; Interventions